Intraoperative malignant glaucoma during femtosecond laser-assisted cataract surgery: A case report. Issue 25 (24th June 2022) - Xu, Rong; Cao, Danmin; Jiao, Ya; Zeng, Qingyan
Abstract: Rationale: Femtosecond laser-assisted cataract surgery (FLACS) has grown in popularity among ophthalmologists as a novel surgical technique. However, malignant glaucoma (MG) is a complication of FLACS. Herein, we report a case of MG following FLACS. Patient concerns: A 66-year-old woman presented with complaints of blurred vision in the right eye and a foreign body sensation in both eyes. Ophthalmological examinations showed that the corrected distance visual acuity was 20/50 and 20/25 in the right and left eyes, respectively. Without any topical anti-glaucoma medication, the intraocular pressure (IOP) was 20 mmHg in the right eye and 17 mmHg in the left eye. Slit-lamp examination of the right eye revealed a transparent cornea with a defect in the punctate overlying epithelium; the central anterior chamber depth was shallow the peripheral iris laser shot was visible, the pupil was normal, and the lens was mainly cortical opacified. Diagnoses: Based on the patient's symptoms, examination results, and preliminary diagnoses, age-related cataract in the right eye, binocular post-antiglaucoma surgery, pseudophakicin in the left eye, and Sjogren syndrome were included. Interventions: FLACS was performed to facilitate anterior capsulotomy and segmentation of the nucleus in the right eye. MG occurred after the femtosecond procedure, and with the treatment of medicines combined with phacoemulsification, IOP was eventually normal without further antiglaucoma therapy. Outcomes: IOP was 16 mmHg on postoperative day 1. Ocular ultrasonography revealed no choroid detachment or hemorrhage in the right eye. Two weeks postoperatively, uncorrected visual acuity was 20/25, and IOP remained normal with no further antiglaucoma treatment on 1 month postoperatively. Conclusions: We describe the occurrence of MG after FLACS and illustrate that miosis and bubble formation after FLACS may be risk factors for MG during FLACS.